Warped Translation Surfaces of Finite Type in Simply Isotropic 3-Spaces - Kelleci, Alev (My University, 2020)
In this paper, we classify warped translation surfaces being invariant surfaces of i-type, that is, the generating curve has formed by the intersection of the surface with the isotropic xz-plane in the three-dimensional simply isotropic space $\\mathbb I^3$ under the condition $\\Delta^{J}x_i=\\lambda_i x_i,$  with J=I,II.  Here, $\\Delta^{J}$ is the Laplace operator with respect to first and second fundamental form and $\\lambda_i$, $i=1,2,3$ are some real numbers. Also, as an application, we give some examples for these surfaces and also some explicit graphics of them. All graphics have been plotted with Maple14.
Keywords: Invariant surface; Laplace operator; Simply isotropic space; Surfaces of finite type